Does the Notion of ‘Doing Well by Doing Good’ Prevail Among Entrepreneurial Ventures in a Developing Nation? - Ahmad, Noor Hazlina; 1964- Ramayah T. (2012)
The rise in ethical and social responsibility awareness in contemporary businesses has led to assumptions that the associated behaviours would enable competitive advantage to be attained as a firm distinguishes itself from its competitors through such practices. This paper reports on a study conducted on the prevalence of such practices among entrepreneurial ventures in an emerging economy (Malaysia), and the effect of such practices on both financial and non-financial performance. A sequential inter-method mixing design was employed in which during stage 1, a series of semi-structured interviews with ten Malaysian SME founder-owners were conducted. Stage 2 involved a survey in which a total of 212 usable questionnaires were received. The results of the first phase of the research (qualitative) found evidence that entrepreneurial ventures in Malaysia do generally engage in both ethical and socially responsible practices. The subsequent model testing using SEM, however, revealed that while ethical practices were positively associated with venture performance, socially responsible practices were not. This may indicate that while entrepreneurial ventures in emerging economies like Malaysia become quickly aware of the more serious consequences of not adopting ethical practices, the concern for social issues may still be lacking, i.e., in terms of motivations, they may be closer to the profitable end of the philanthropy versus profitability spectrum. While the findings may be equivocal, we believe that the paper makes the following two significant contributions: (1) it provides an empirical test of the importance of ethical and socially responsible practices to entrepreneurial venture performance and (2) it furthers understanding of how and why this may be different in an emerging economy context.
Keywords: business success; Developing nation; Entrepreneurial ventures; Social Responsibility; ethical practices